Effects of Geographical Origin and Timing of Broodstock Collection on Hatchery Conditioning of the Clam Ruditapes decussatus (L. 1758) - Rania Azirar; Samah Fettach; Fiz da Costa; Montse Pérez; Abderrahim Chiaar; Adil Aghzar; Yassine Ouagajjou (Animals)
The grooved carpet shell clam (Ruditapes decussatus), widely found along Morocco’s coasts and estuaries, is a key economic resource due to its high market value. However, clam production has declined over recent decades, largely due to the overexploitation of natural beds, and recruitment failures, leading to a limited wild spat availability. This study examined how the broodstock collection season (winter vs. summer) and origin (South Atlantic vs. North Mediterranean) affect broodstock performances in hatcheries. The maturity development (condition index (CI) and gonadal condition index (GCI)), histological examination, and reproductive output were evaluated. The results showed that Mediterranean clams achieved a higher maturity during winter conditioning (CI = 13.60 ± 1.02, GCI = 6.01 ± 0.90) than the Atlantic population (CI = 11.51 ± 1.50, GCI = 5.31 ± 1.14). Moreover, Mediterranean clams produced more oocytes per female (2.34 million), despite the lower spawning rate (42%), compared to the Atlantic clams (1.68 million) with a 69% spawning rate by the end of the winter conditioning. These findings highlight the importance of selecting broodstock by geographic origin to optimize shellfish hatchery production.